Disease progression in idiopathic pulmonary fibrosis under anti-fibrotic treatment - Cilli, Aykut; Uzer, Fatih (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Idiopathic pulmonary fibrosis (IPF) is the most common progressive interstitial disease of unknown etiology. The course of disease is not possible to predict. Frequent monitoring using multiple assessments is important to evaluate disease progression. Currently, there is no consensus on how progression should be defined. Nintedanib and pirfenidone slow the progression of IPF, but the disease can progress even under anti-fibrotic treatment. The goal of this review is to examine and summarize the current data about IPF progression in patients who were on anti-fibrotic treatment. Also, we outline the limitations of the tests used for disease progression.